ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI IBU PADA PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) - Sri Mulia Sari sari; Dea Mega Arini; Putinah; Nelly Mariyam (Jurnal Kesehatan dan Pembangunan, 2022)
Cervical cancer is one of the most common types of cancer in women and is terrible, considering the level of danger of the disease. The purpose of this study was to determine the relationship between husband's support and mother's motivation during the Visual Inspection of Acetic Acid (IVA) at the Gandus Health Center Palembang in 2021. The design of this study was an analytical descriptive design using a cross sectional approach. The sampling technique used the Probability Sampling technique as many as 39 respondents at the Gandus Health Center Palembang from April to July 2021. The results of this study were univariate research. It was found that respondents who had good husband support were (61.5%), respondents who had strong motivation were (59 .0%) and the results of the bivariate study found that there was a relationship between husband's support and respondent's motivation at the Gandus Palembang Health Center in 2021 with a p value of 0.035. The conclusion of this study is that there is a relationship between husband's support and respondent's motivation at the Gandus Health Center Palembang in 2021 with a p value of 0.035.